Common risk factors for major noncommunicable disease, a systematic overview of reviews and commentary: the implied potential for targeted risk reduction. (October 2019) - Peters, Ruth; Ee, Nicole; Peters, Jean; Beckett, Nigel; Booth, Andrew; Rockwood, Kenneth; Anstey, Kaarin J.
Noncommunicable disease now contributes to the World Health Organization top 10 causes of death in low-, middle- and high-income countries. Particular examples include stroke, coronary heart disease, dementia and certain cancers. Research linking clinical and lifestyle risk factors to increased risk of noncommunicable disease is now well established with examples of confirmed risk factors, including smoking, physical inactivity, obesity and hypertension. However, despite a need to target our resources to achieve risk reduction, relatively little work has examined the overlap between the risk factors for these main noncommunicable diseases. Our high-level review draws together the evidence in this area. Using a systematic overview of reviews, we demonstrate the likely commonality of established risk factors having an impact on multiple noncommunicable disease outcomes. For example, systematic reviews of the evidence on physical inactivity and poor diet found each to be associated with increased risk of cancers, coronary heart disease, stroke, diabetes mellitus and dementia. We highlight the potential for targeted risk reduction to simultaneously impact multiple noncommunicable disease areas. These relationships now need to be further quantified to allow the most effective development of public health interventions in this area.